PENGARUH PEMBERIAN PUDING LIDAH BUAYA TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL PENDERITA HIPERKOLESTEROLEMIA RAWAT JALAN PUSKEMAS GENUK KOTA SEMARANG - Rizki Dyah Anggraeni; Setyo Prihatin; Ana Yuliah Rahmawati (JURNAL RISET GIZI, 2018)
Background  : Hypercholesterolemia is a condition in which the total blood cholesterol level exceeds the normal value reaching ≥200 mg / dl. To reduce total cholesterol levels can be done by regulating the intake of macro nutrients and micronutrients, one of which is fiber. Polysaccharide food fiber type hemicellulose which is glucomannan contained in aloe vera can reduce total cholesterol levels in the blood. Objective  : To know influence of giving aloe vera pudding on total cholesterol levels of Patients with Hypercholesterolemia Outpatient at Puskesmas Genuk Semarang City.Method  : This research used method quasi experimental with research design control group pre test post test. Taking sample on a random as many as 34 people for 2 groups that is treatment and control. The treatment group was given 100 grams of aloe vera for 14 days. Measurement of total cholesterol levels was carried out before and after the intervention. Fiber and fat intake subject before and during the intervention with 24-hour food recall method, while measurement activity physical use method IPAQ. Analysis statistics use Independent t-test, Paired t-test, and Anovarepeated measure.Result  : There were differences in changes in total cholesterol levels between groupstreatment and control were significant (p = 0.026) and there was a significant decrease in total cholesterol levels (p = 0.009) of -44.70 ± 56.51 in the treatment group given aloe vera pudding. Conclusion  : Giving 100 grams of aloe vera pudding for 14 days could decrease total cholesterol levels of hypercholesterolemia patients of Puskesmas Genuk Semarang City.